The Symbolic Values of the Injak Telur Tradition in Marriage: A Living Hadith Study in Taktakan Village, Serang, Banten - Izar Mutaqin; Muhammad Alif (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to examine the injak telur (egg-stepping) tradition in customary wedding processions in Taktakan Village, Serang City, Banten Province, Indonesia, with a focus on its symbolic meanings as a manifestation of Living Hadis in society. The primary research question explores the extent to which hadis values are alive and actualized through this ritual practice. Employing a qualitative field study with phenomenological and social action approaches, primary data were collected via participatory observation, in-depth interviews, and documentation from key informants, including customary leaders, tradition practitioners, and local residents. The findings reveal that the injak telur tradition serves not only as a preserved customary ritual but also as a medium for actualizing hadis values in the marital context. Its symbolic meanings encompassing the husband's responsibility as head of the family, the wife's devotion and cooperation, household harmony, and aspirations for generational continuity align with marital advice in authentic hadis, particularly those narrated by al-Bukhari and an-Nasa'i. The community in Taktakan Village interprets this tradition through a process of contextualizing hadis texts into daily religious practices, thereby forming an implicit Living Hadis. This study concludes that the injak telur tradition can serve as an effective means of marital counseling for couples to realize a sakinah (tranquil, peaceful) family.